Export-import food calorie of Russia - T. Yu. Shabanov (Овощи России, 2020)
Relevance. A possible scenario of state self-isolation during an emergency actualizes interest in the study of foreign trade turnover of food calories as a factor of national security.Methods. The article considers issues of caloric value of export and import of the Russian food market for period 1998-2017.Results. The study was based on some hypothesis that the calorie content of exported grain was higher than a import of low-calorie foods like vegetables, fruits, and dairy products. The testing this hypothesis showed a sixfold excess of food calorie content of export over import and h a seven-fold cheapness of exported calories over imported ones. It was revealed that exports was represented by plant calories (grain), and import was represented by animal calories (dairy products). It was proposed to freeze the export of plant calories into emergency period and redirecting to development of domestic animal calories.